Surface functionalized exosomes as targeted drug delivery vehicles for cerebral ischemia therapy - Tian, Tian; Zhang, Hui-Xin; He, Chun-Peng; Fan, Song; Zhu, Yan-Liang; Qi, Cui; Huang, Ning-Ping; Xiao, Zhong-Dang; Lu, Zu-Hong; Tannous, Bakhos A.; Gao, Jun (Biomaterials, 2018)
The safe and effective delivery of drugs is a major obstacle in the treatment of ischemic stroke. Exosomes hold great promise as an endogenous drug delivery nanosystem for the treatment of cerebral ischemia given their unique properties, including low immunogenicity, innate stability, high delivery efficiency, and ability to cross the blood-brain barrier (BBB). However, exosome insufficient targeting capability limits their clinical applications. In this study, the c(RGDyK) peptide has been conjugated to the exosome surface by an easy, rapid, and bio-orthogonal chemistry. In the transient middle cerebral artery occlusion (MCAO) mice model, The engineered c(RGDyK)-conjugated exosomes (cRGD-Exo) target the lesion region of the ischemic brain after intravenous administration. Furthermore, curcumin has been loaded onto the cRGD-Exo, and administration of these exosomes has resulted in a strong suppression of the inflammatory response and cellular apoptosis in the lesion region. The results suggest a targeting delivery vehicle for ischemic brain based on exosomes and provide a strategy for the rapid and large-scale production of functionalized exosomes.